Assessing traditional Chinese medicine from a molecular perspective - Minhui Su; Wenxi Wang; Xudong Sun; Lihong Li; Weihong Tan (Journal of Traditional Chinese Medical Sciences)
Molecular medicine, which delves into the intricacies of biomolecular structure, function, and role, is pivotal for advancing precise diagnostics and personalized treatment. Nucleic acids, a class of star functional molecules, are notable for their versatile applications in molecular diagnostics, gene therapy, and drug development. Therefore, in this study, we review the extensive use of nucleic acid aptamers in medicinal practice. Furthermore, the expanding field of molecular medicine has catalyzed advancements in traditional Chinese medicine (TCM), as evidenced by scientific endeavors to integrate modern technologies. Therefore, TCM has experienced rapid modernization by leveraging artificial intelligence, nucleic acid molecular medicine, and bioelectronic medicine.